A Symbiotic Link Between Music, Movement, and Social Emotional Learning: Mindful Learning in Early Learners - Matt Yanko; Priscilla Yap (LEARNing Landscapes, 2020)
In the following study we investigate how young learners engage with music and movement to illustrate their understandings and connections to nature. We discover a symbiotic relationship between the performing arts, Social Emotional Learning, and Mindful Learning over the course of six months, and examine the potentials and constraints of this harmonization. Results from this study show that learning in a co-constructivist setting, which allows opportunities for reflective listening, choice, intentional focus, and feedback, supports the development of behavioural and emotional abilities, and empowers students to delve deeper into their connections with nature through composing abstract music and movement pieces.